Oxfordian sponge association from the Neuquén basin, Mendoza,west central Argentina - Beresi, Matilde Sylvia (2003)
This paper describes an Upper Jurassic association of siliceous sponges from the Neuquén basin, southern Mendoza province, at Ŕo Potimalal. Wackestones crop out in this stratigraphic section, and massive sponge-bearing micritic limestones of the La Manga formation (Plicatilis zone) have been deposited in outer shelf to slope settings. Sponges are regularly preserved as whole bodies. Their skeletons are mostly calcified, but the skeletal siliceous structure is sometime preserved. The siliceous sponges belong to the Order Hexactinosa (Class Hexactinellida, Subclass Hexasterophora) (Laocoetis sp., L. parallela, L. procumbens, Cribrospongia sp., C. clathrata, C. cucullata, Ordinatus sp., Linonema calyx ) and Lyssakinosa (Poligonatyum sphaeroides). The majority of the sponge specimens correspond to the Families Cribrospongiidae (genus Cribrospongia) and Laocoetidae (genus Laocoetis). The Upper Jurassic carbonates are interpreted as deposits of a highstand systems tract, similar to other Oxfordian sequences found around the world. © 2003 Elsevier Ltd. All rights reserved.